Conventional Versus an Early Start of Iron Supplementation in Premature Newborns - Mohtarama Mostari; Abdullahel Amaan; Afroza Islam; Md. Morshed Monzur Kabir; M. A. Mannan (Reproductive, Female and Child Health)
ABSTRACT Background Iron deficiency is more common in preterm infants. This study was aimed to evaluate the effect of early and conventional late start of supplemental iron in preterm newborns. Methodology This Randomized Controlled Trial was conducted in the Department of Neonatology, Bangabandhu Sheikh Mujib Medical University, Dhaka. A total 21 preterm newborn were included in early intervention (EI) group, where iron was introduced at 2 weeks of age and 19 in the late intervention (LI) group, where it was introduced at 6 weeks of age. Sample for CBC, red cell indices, S. ferritin and C‐reactive protein was evaluated at admission, pre‐intervention sample at 2 weeks and 6 weeks in EI and LI group respectively and follow up sampling at 12 weeks. Weight, length and head circumference were measured at birth, 2 and 12 weeks of age in early group and at birth and 6 and 12 weeks in late group. At 12 weeks of age neurodevelopment was assessed. Result Mean gestational age was 33.52 ± 1.91 and 33.48 ± 1.46 weeks in early and late group respectively. The mean S. Ferritin was significantly higher in EI group (92.75 ± 47.33 ng/mL) than the LI group (56.95 ± 35.06 ng/mL), p = 0.01. Neurodevelopmental score evaluated by Bayley Scale III showed mean cognitive score (p = 0.973), mean motor score (p = 0.859), mean language score were (p = 0.511) in EI and LI group were not significantly comparable. Conclusion An early start of iron supplementation at 2 weeks of age in preterm newborn results in significantly higher serum ferritin level than when it is started late. Trial Registration The study was conducted after ensuring a clinical trial registration and approval from institutional review board (IRB) of Bangabandhu Sheikh Mujib Medical University (BSMMU). An informed written consent was ensured from the parents of each of the participants.